2020
DOI: 10.1186/s40657-020-00194-w
|View full text |Cite
|
Sign up to set email alerts
|

Whole genome phylogeny of Gallus: introgression and data-type effects

Abstract: Background: Previous phylogenetic studies that include the four recognized species of Gallus have resulted in a number of distinct topologies, with little agreement. Several factors could lead to the failure to converge on a consistent topology, including introgression, incomplete lineage sorting, different data types, or insufficient data. Methods:We generated three novel whole genome assemblies for Gallus species, which we combined with data from the published genomes of Gallus gallus and Bambusicola thoraci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 86 publications
1
16
1
Order By: Relevance
“…The tight linkage between coding and non-coding in the Prum dataset makes this study an excellent complement to Reddy et al [13], which compared trees estimated using unlinked coding and non-coding data. When the evidence for data type effects in this study is combined with the results of Reddy et al [13] and Jarvis et al [11] they provide strong evidence that the important variable is the data types and not any idiosyncratic features of specific genomic regions in each study, Data type effects have been described in a number of studies, though the nature of the effects range from those that are quite subtle [49,53] to much stronger effects [11,13,[18][19][20][21][22][23]. Some reported examples of data type effects reflect analyses of the same coding regions as nucleotides and after translation to amino acids [18,[54][55][56].…”
Section: The Role Of Data Types In Phylogenomic Analysessupporting
confidence: 56%
See 1 more Smart Citation
“…The tight linkage between coding and non-coding in the Prum dataset makes this study an excellent complement to Reddy et al [13], which compared trees estimated using unlinked coding and non-coding data. When the evidence for data type effects in this study is combined with the results of Reddy et al [13] and Jarvis et al [11] they provide strong evidence that the important variable is the data types and not any idiosyncratic features of specific genomic regions in each study, Data type effects have been described in a number of studies, though the nature of the effects range from those that are quite subtle [49,53] to much stronger effects [11,13,[18][19][20][21][22][23]. Some reported examples of data type effects reflect analyses of the same coding regions as nucleotides and after translation to amino acids [18,[54][55][56].…”
Section: The Role Of Data Types In Phylogenomic Analysessupporting
confidence: 56%
“…For this. study define data type effects in a simple and empirical manner: data type effects are those cases where phylogenetic analyses of distinct subsets of the genome defined using non-phylogenetic criteria (e.g., structural or functional criteria) yield different results [1,13,24,49]. It is necessary to restrict consideration to data types dispersed across the genome so discordant histories for individual genes [50,51] do not obscure the data type dependence (if it exists).…”
Section: The Role Of Data Types In Phylogenomic Analysesmentioning
confidence: 99%
“…Herein, we combine estimates of CBL obtained using genome-scale indel data with information from timetrees and reconstructions of ancestral generation times to yield what we believe to be the first empirical estimates of the relative effective population size (Ne of ancestral lineages in very deep time. Our approach bears some similarity to recently described approaches [81,82] and those of Tiley et al [83], who estimated CBL using binary data (TE insertions and "perfect" transversions, respectively). However, we implemented these analyses in a modified version of the commonly used multispecies coalescent program Accurate Species TRee Algorithm (ASTRAL) [84,85].…”
Section: Introductionmentioning
confidence: 65%
“…Alternatively, one might estimate the timetree using loci selected from parts of the genome where Ne is reduced locally. Tiley et al [83] reported that conserved non-exonic elements (from Edwards et al [114]) had shorter internal branch lengths than any other data type they examined. They proposed that this reflects a reduction in SPILS due to local reductions in Ne driven by Hill-Robertson interference [115].…”
Section: Biases Associated With Relaxed Clock Analysesmentioning
confidence: 92%
See 1 more Smart Citation